Diwa't kapookan (Manila NCCA, Metropolitan Museum of Manila, 2006)
Contains winners of the 2005 and 2006 Websining Digital Art Competition 9-23 March 2006, Upper Galleries, Metropolitan Museum of Manila and also includes articles, discussions, messages and excerpts of the forum on digital art.
CD
Fatima Lasay, curator.
Keywords: Digital art; Art -- Competitions